2013
DOI: 10.1158/1078-0432.ccr-13-1093
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Single-Nucleotide Polymorphisms in the PI3K–PTEN–AKT–mTOR Pathway and Increased Risk of Brain Metastasis in Patients with Non–Small Cell Lung Cancer

Abstract: Purpose: Non-small cell lung cancer (NSCLC) metastasizes fairly often to the brain, but identifying which patients will develop brain metastases is problematic. The phosphoinositide 3-kinase (PI3K)-AKTmTOR signaling pathway is important in the control of cell growth, tumorigenesis, and cell invasion. We hypothesized that genotype variants in this pathway could predict brain metastasis in patients with NSCLC.Methods: We genotyped 16 single-nucleotide polymorphisms (SNP) in five core genes (PIK3CA, PTEN, AKT1, A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 40 publications
3
56
1
Order By: Relevance
“…The remaining 18 articles were reviewed and, 8 of them were removed due to lack of sufficient data or examing other mTOR polymorphisms but not rs2295080, rs2536 (T>C) and rs11121704 [26][33]. Finally, 10 studies were met the inclusion criteria [12][20], [35], and 6 studies evaluated the influence on cancer risks [12][13], [15][18] and 3 assessed the clinical outcomes [19], [20], [35], such as death, metastasis, resistance to chemotherapy, and toxicity, and one examined both [14]. The flow of study identification, inclusion, exclusion was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 18 articles were reviewed and, 8 of them were removed due to lack of sufficient data or examing other mTOR polymorphisms but not rs2295080, rs2536 (T>C) and rs11121704 [26][33]. Finally, 10 studies were met the inclusion criteria [12][20], [35], and 6 studies evaluated the influence on cancer risks [12][13], [15][18] and 3 assessed the clinical outcomes [19], [20], [35], such as death, metastasis, resistance to chemotherapy, and toxicity, and one examined both [14]. The flow of study identification, inclusion, exclusion was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The genotypes in the controls in all studies were in Hardy-Weinberg equilibrium. For estimating the influence of mTOR polymorphisms (rs2295080 and rs11121704) on clinical outcomes in cancer patients, 4 eligible studies included 1594 cancer patients, were identified: 2 were conducted in USA [19], [20] and two were in China [14], [35]. Two studies in USA evaluating evaluated more than one clinical outcome parameter, and these parameters were separately analyzed as separate observations.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that genetic variations in the phosphoinositide 3-kinase-AKT pathway are associated with an increased risk of BM in patients with NSCLC. 16 Additional investigations on candidate genes that are crucial for metastasis may uncover missing links in the heritability of BM. Autophagy is an important adaptive prosurvival mechanism that mediates cancer cell survival during metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the association remained significant after the Bonferroni correction for AKT1: rs2494732 (i.e., <0.05/16 ¼ 0.003) in our study. Otherwise, AKT1:rs2498804 and rs2494732 were in strong linkage disequilibrium (D ¼ 0.95), and we believe that AKT1: rs2498804 is not a false-positive gene (1). In addition, we are pleased to find that the association of AKT1:rs2498804 was confirmed in your independent cohorts.…”
mentioning
confidence: 76%